2023
DOI: 10.3389/fmicb.2022.1076577
|View full text |Cite
|
Sign up to set email alerts
|

Activities and metabolomics of Cordyceps gunnii under different culture conditions

Abstract: Many active metabolites have been identified from various species of the fungal genus Cordyceps. A predominant species of this genus is Cordyceps gunnii, but there are limited reports on the active ingredients from this species. This study aimed to conduct activity assays and metabolome analysis on extracts of C. gunnii obtained under different culture conditions. Five different solid media were selected to culture the mycelium of C. gunnii and the metabolites were extracted with organic solvents; concurrently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Consequently, researchers have focused on exploring the activities and components of their anamorphs. In a previous study, we screened P. gunnii YMF1.00003 under different culture conditions through the conduct of metabolome analysis and activity comparison and found that the fermentation extract of the mycelium in WGA was similar to the extract of stroma and host complexes and had obvious cytotoxic activity ( Qu et al, 2022 ). Therefore, we further examined the metabolites and activities of P. gunnii YMF1.00003 fermented in two different media.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, researchers have focused on exploring the activities and components of their anamorphs. In a previous study, we screened P. gunnii YMF1.00003 under different culture conditions through the conduct of metabolome analysis and activity comparison and found that the fermentation extract of the mycelium in WGA was similar to the extract of stroma and host complexes and had obvious cytotoxic activity ( Qu et al, 2022 ). Therefore, we further examined the metabolites and activities of P. gunnii YMF1.00003 fermented in two different media.…”
Section: Discussionmentioning
confidence: 99%
“…The wild stroma and host complexes of Cordyceps fungus have been a focal point of research, but their scarcity has led researchers to concentrate on clonal mycelium. In the initial stages, we evaluated the Paecilomyces gunnii extracts under different culture conditions and from the wild stroma and host complexes through the performance of a metabolome analysis and identified the culture conditions for producing metabolites with enhanced cytotoxic activity ( Qu et al, 2022 ). In the present study, fermentation was conducted under screened culture conditions to yield active natural products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations